NURTURING WELL-BEING: EXPLORING THE INTERPLAY OF SELF-COMPASSION, SELF-AFFIRMATION, AND DEPRESSION IN UNDERGRADUATE NURSING STUDENTS - Saito , Yuki; Nakamura, Akira (American Research Journal of Nursing and Health Sciences (ARJNHS), 2024)
The escalating demand for nurses in Japan, driven by factors such as the impact of new coronavirus infections and an aging population, has led to a surge in the number of nursing schools and universities. Despite a seemingly full university enrollment era attributed to a declining population under 18 years, the nursing workforce continues to expand, totaling approximately 1.27 million according to the Japan Nurses Association. However, the profession grapples with a persistent challenge – a high turnover rate among nurses. This study delves into the intricacies of the nursing profession in Japan, with a particular focus on the factors contributing to the high turnover rate. Notably, nurses often internalize others' distress, leading to empathy fatigue and self-negative cognitions due to secondary stress. This phenomenon has been identified as a significant precursor to burnout, underscoring the critical need for self-compassion in the nursing domain. The research aims to explore the relationship between empathy fatigue, self-negative cognitions, and the resultant burnout experienced by nurses in Japan. Drawing on existing literature and empirical data, the study investigates the psychological toll of continuously perceiving others' distress as one's own and its implications for the well-being and job satisfaction of nurses. Furthermore, the research will delve into the role of self-compassion as a potential mitigating factor against burnout in the nursing profession. Understanding the unique challenges faced by nurses in Japan is crucial for the development of targeted interventions and support mechanisms. By shedding light on the psychological aspects contributing to the high turnover rate, this study aspires to inform policies and practices that foster a more compassionate and sustainable work environment for nurses. The findings are anticipated to contribute not only to the improvement of nurses' well-being but also to the overall enhancement of healthcare services in the country.